2016
DOI: 10.1074/jbc.m116.732503
|View full text |Cite
|
Sign up to set email alerts
|

A Camelid-derived Antibody Fragment Targeting the Active Site of a Serine Protease Balances between Inhibitor and Substrate Behavior

Abstract: A peptide segment that binds the active site of a serine protease in a substrate-like manner may behave like an inhibitor or a substrate. However, there is sparse information on which factors determine the behavior a particular peptide segment will exhibit. Here, we describe the first x-ray crystal structure of a nanobody in complex with a serine protease. The nanobody displays a new type of interaction between an antibody and a serine protease as it inserts its complementary determining region-H3 loop into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…These results were later replicated independently using additional V H s, 51 V H Hs 11,47,48 and V NAR s 12 directed against the active site of lysozyme, as well as with active site-binding V H Hs against α-amylase, 31,32 carbonic anhydrase, 32 and urokinase. 62,63 Inhibition of α-amylase was achieved by one V H H through penetration of the active site cleft with its CDR2 loop, 31 demonstrating that CDR3-centric binding is not the only mechanism of competitive enzyme inhibition by sdAbs. Competitive inhibition of these enzymes by conventional antibodies targeting their active sites has not been described despite intensive study, especially of murine antibodies against lysozyme.…”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%
“…These results were later replicated independently using additional V H s, 51 V H Hs 11,47,48 and V NAR s 12 directed against the active site of lysozyme, as well as with active site-binding V H Hs against α-amylase, 31,32 carbonic anhydrase, 32 and urokinase. 62,63 Inhibition of α-amylase was achieved by one V H H through penetration of the active site cleft with its CDR2 loop, 31 demonstrating that CDR3-centric binding is not the only mechanism of competitive enzyme inhibition by sdAbs. Competitive inhibition of these enzymes by conventional antibodies targeting their active sites has not been described despite intensive study, especially of murine antibodies against lysozyme.…”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%
“…B) that assist in stabilizing the conformation of these CDRs and the overall stability of the domain (Govaert et al ., ). The small size and long CDRs of Nbs allow them to successfully target enzymatic clefts located within concave epitopes of enzymes and proteases (Lauwereys et al ., ; Conrath et al ., ; Kromann‐Hansen et al ., ), and conserved inner regions of surface proteins from pathogens, frequently less accessible to the larger conventional Abs (Stijlemans et al ., , ; Rossey et al ., ). Nbs have been used as stabilization agents in crystallographic studies (Ring et al ., ; Hassaine et al ., ; Pardon et al ., ) and as molecular probes in cell biology for visualization of proteins in living cells (Helma et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, their CDR‐H3s are flexible or close to the catalytic center enough that leads slow cleavage at the scissile bond by cdMMP‐14. Mutation studies of a camelid nanobody uPA inhibitor Nb4 revealed that an intra‐loop interaction network within CDR‐H3 balances its inhibitor versus substrate behavior . Certainly, whether a similar molecular mechanism is applied for 3A2 mutants identified here can only been fully elucidated by a comprehensive epitope/paratope mapping or structure determination.…”
Section: Discussionmentioning
confidence: 91%
“…Mutation studies of a camelid nanobody uPA inhibitor Nb4 revealed that an intra-loop interaction network within CDR-H3 balances its inhibitor versus substrate behavior. 30 Certainly, whether a similar molecular mechanism is applied for 3A2 mutants identified here can only been fully elucidated by a comprehensive epitope/paratope mapping or structure determination. Although standard mechanism is an effective and potent inhibition paradigm, most standard mechanism protease inhibitors tend to have relatively broad specificity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation